Fabrication and Characterization of Polycaprolactone (PCL)-Silk-Hydroxyapatite (HA) based scaffold - Zubir, Nazira; Pingguan-Murphy, Belinda; Azari, P. (2016)
One of the key aspects that need to be addressed and considered in scaffold fabrication is nanofibres structure. Nanofibrous is one of the most suitable form of artificial matrices for cell growth and proliferation. Electrospinning technique is capable to fabricate polymeric nanofibers with high surface area. Silk, a natural polymer has astounding properties such as biocompatible, biodegradable and bioresorbable. As a result, silk which mimic and analogous to native extracellular matrix (ECM) have been used extensively in the fields of tissue engineering and biomaterials. In the present study, Polycaprolactone (PCL) and Hydroxyapatite (HA) were blended with silk to enhance the mechanical property of the composite scaffold. HA is known for its osteoconductivity while PCL could further enhance the mechanical property of silk. Fourier Transform Infrared (FTIR) spectroscopy and Field Emission Scanning Electron Microscopy (FESEM) methods were used to characterize the PCL-Silk-HA based scaffold. The FESEM results show that the diameter of the fibres were further reduced with the presence of Silk and HA when compared to PCL alone. The FTIR spectra for both PCL-Silk and PCL-Silk-HA based scaffolds revealed the existence of the beta sheet secondary protein structure of the silk protein with the emergence of new characteristic peaks of amide I and amide II at 1645 1/cm and 1488 1/cm respectively. The transmission peak for C-O stretching of PCL based scaffold, at 1206.5 1/cm is observed to have drastically reduced in the PCL-Silk as well as PCL-Silk-HA based scaffold. The phosphate groups are observed at 1131 1/cm, 1000 1/cm and additional phosphate group is shown at 600.87 1/cm peak when HA is presence. These results indicate that all three types of materials have formed a composite structures through chemical bonding.